2008
DOI: 10.1111/j.1574-6941.2008.00474.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical organization and phylogenetic analysis of acdR as leucine-responsive regulator of the 1-aminocyclopropane-1-carboxylate deaminase gene acdS in phytobeneficial Azospirillum lipoferum 4B and other Proteobacteria

Abstract: The phytostimulatory alphaproteobacterium Azospirillum lipoferum 4B exhibits the plant-beneficial gene acdS, which enables deamination of the ethylene precursor 1-aminocyclopropane-1-carboxylic acid (ACC). Here, we show that acdS is in the vicinity of acdR, a homolog to leucine-responsive regulator lrp, in A. lipoferum 4B and most other acdS+ Proteobacteria. Unlike in Beta- and Gammaproteobacteria, acdS (and acdR) is preferentially located on symbiotic islands and plasmids in Alphaproteobacteria. In A. lipofer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 69 publications
7
39
0
1
Order By: Relevance
“…Moreover, due to intragenomic transfer events, many microorganisms may have lost acdS genes. Consistently, it has been reported that, during phenotypic variation events, A. lipoferum strain 4B readily loses the plasmid containing an acdS gene (Prigent-Combaret et al, 2008).…”
Section: Distribution and Phylogeny Of Acc Deaminasesupporting
confidence: 82%
“…Moreover, due to intragenomic transfer events, many microorganisms may have lost acdS genes. Consistently, it has been reported that, during phenotypic variation events, A. lipoferum strain 4B readily loses the plasmid containing an acdS gene (Prigent-Combaret et al, 2008).…”
Section: Distribution and Phylogeny Of Acc Deaminasesupporting
confidence: 82%
“…A model was proposed to explain how bacteria harboring the ACC deaminase activity could lower ET amount in plant cells (Glick et al 1998 ). This model is valid for certain Azospirillum strains that have ACC deaminase activity (Blaha et al 2006 ;Prigent-Combaret et al 2008 ). The ACC deaminase degrades ACC, the ET precursor.…”
Section: Against Abiotic Stressesmentioning
confidence: 95%
“…4). ACC deaminase (encoded by the acdS gene) catalyses the conversion of ACC, the immediate plant precursor for ethylene, into NH 3 and α-ketobutyrate and is widely distributed in soil fungi and bacteria, especially the Proteobacteria (Blaha et al 2006;Prigent-Combaret et al 2008). Whilst the ecological significance of ACC-deaminase in soil microorganisms is largely unknown, in plant-beneficial bacteria it may serve to diminish the amount of ACC available for production of ethylene (Glick et al 2007a).…”
Section: Microbial Enzymatic Activities Influencing Plant Hormone Levelsmentioning
confidence: 98%